(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
It is of utmost importance for English teachers to help students to enhance speaking abilities. Humour has always been seen as enhancement to classroom teaching and learning. Over time, the problem of humour caught the attention of many thinkers. In language teaching, a teacher can easily see that the learners are often motivated greatly when humour is used in classroom. Teachers’ effective use of humor is generally viewed as a positive factor in the classroom and it is often identified as a teaching technique for developing a positive learning environment. In the present article the role of humour is shown in promoting speaking through some elements of humour.